Librarians and professional status : continuing professional development and academic libraries - Roberts, Norman (Library Association, 1991)
In this work the strivings of the library professions in the USA and UK for professional recognition are examined against the wider social trends and technological developments. It looks in particular at the case of academic librarians, and charts their evolving status